Abschätzung der Wahrscheinlichkeit einer Bewirtschaftungsaufgabe landwirtschaftlicher Parzellen mittels GIS-gestützter Modellierung (PROBAT) - Veronika Asamer; Michael Braito; Klara Breitwieser; Barbara Enengel; Rainer Silber; Hans Karl Wytrzens (Universität für Bodenkultur Wien, Department für Wirtschafts- und Sozialwissenschaften, Institut für nachhaltige Wirtschaftsentwicklung, 2009)
– Local abandonment of agricultural land in less favoured areas is a serious issue as well as for farmers as for governments. In this article we analyze in the case of two cadastral municipalities in Upper Austria, which socioeconomic and biophysical factors enhance the retreat of agricultural land use. The particular reflection of characteristics on the level of cadastral parcels shows a highly significant influence of exposition and soil quality as well as of socioeconomic (type of farming, labour capacity, follow-up, age, participation in ÖPUL) factors. Aim of the research project was to develop a GIS-based method to assess the risk of abandonment of agricultural parcels in future. Factors which lead to abandonment of agricultural land were collected in form of a model. This explanation model was extended to a forecasting model which is based on probability assessment. The forecasting model operates at parcel level and combines bio-physical factors with socio-economic determinants. The model is built on marginal gain theory as well as on considerations of behaviour models. The forecasting model was verified and represents an all-purpose early warning system to identify retreating agricultural land at a prediction horizon of 10 years. The results of the research could be the basis of further scientific analyses (development of fallow land, scenarios of future land use); future planning decisions or the effective use of subsidies should be facilitated.
Keywords: R52; 330; land use change; marginal revenue of land use; modelling; land abandonment; risk evaluation; binary logistic regression; GIS